A rare case of bladder cancer that metastasized to brain, heart, and lung lymph nodes benefited from immunotherapy - Zhu, Lian-Kai; Li, Zhong-Jian; Wang, Zhi-Bo; Chen, Jin-Tao; Zhang, Hua-Jun; Zhao, Xu-Wei; Liu, Hong-Yao (World Journal of Surgical Oncology, 2022)
AbstractBladder cancer is a common malignant tumor of the genitourinary system, with the primary cause of death being metastasis. The most common metastatic sites are the lymph nodes, liver, lung, bone, peritoneum, pleura, kidney, adrenal gland, and the intestine. Brain and heart metastases are rare. In this report, we describe a patient who had pulmonary lymph node metastases more than a year after being diagnosed with bladder cancer, followed by brain and cardiac metastases more than two years later. Following the failure of standard first-line chemotherapy, the patient accepted 6 cycles of tislelizumab immunotherapy. The re-examination revealed that the bilateral frontal brain metastases had vanished, the right temporal lobe metastases had been greatly decreased, the neurological symptoms had been alleviated, and the cardiac metastases had disappeared. This is a rare clinical case with encouraging effects of tislelizumab and can serve as a model for the treatment of similar patients.